Structural equation modeling of the relationship between character strengths and marital relationship quality: The mediating role of integrative self-knowlege - Hannaneh Sadeghi; Mehrangiz Shoaa kazemi; Jaafar Moharami (مجله علوم روانشناختی)
Background: Personality traits are one of the most important factors in preserving and disintegrating the family. People who have adaptive behaviors and can manage their unpleasant and negative emotions experience better relationships. Therefore, it is necessary to investigate the role of psychological factors in the quality of couples' relationships. Aims: The present study aimed to investigate the relationship between character strengths and marital relationship quality using structural equation modeling, with integrative self-knowlege as a mediator. Methods: The current descriptive and correlational research was conducted using structural equation modeling. The statistical population of this research consisted of all married men and women living in Tehran in 1402. The sample was 392 people who were randomly selected in a multi-stage cluster. In order to collect data, questionnaires of the quality of couple relationships were used by Kundi et al. (2016), Patterson and Sigelman's character abilities (2004), Ghorbani et al.'s (2008) cohesive self-knowledge. In order to evaluate the proposed model, structural equation modeling was used using AMOS and SPSS-27. Results: The results indicated that the structural model of the relationship between character strengths and marital relationship quality with integrative self-knowlege as a mediator fit the data well. Both character strengths and integrative self-knowledge were found to have direct and positive effects on marital relationship quality. Additionally, character strengths indirectly influenced marital relationship quality through integrative self-knowledge (β= 0.174, P< 0.001). These findings suggest that enhancing character strengths, both directly and indirectly through the influence of integrative self-knowlege, can play a significant role in improving marital relationship quality. Conclusion: The findings of the present study contribute to a clearer understanding of the concept, dimensions, and factors influencing marital relationship quality. This knowledge can serve as a basis for strategic decision-making aimed at strengthening families. Moreover, the study can lead to a deeper understanding of the concept of marital relationship quality and complement existing theories in this field.